Controlling the spatial distribution of quantum dots in nanofiber for light-harvesting devices - Choi, Yung Ji; Hwang, Daesub; Chung, Heejae; Kim, Dong Young; Kim, Dongho (NATURE PUBLISHING GROUP, 2015)
The ability to control inter-dot or inter-molecule spacing of functional moieties in solid-state devices has long been studied for both fundamental and technological reasons. In this study, we present a new strategy for controlling the distance between quantum dots (QDs) based on one-dimensional spatial confinement in a polymer nanofiber template. This reliable technique allows for the isolation of QDs at a sufficient distance in a thin film and retains their monomeric character, with distinct spectra from aggregates (similar to 30-nm shift) and monoexponential photoluminescence decay, indicating the suppression of inter-dot interactions. We successfully developed light-harvesting devices by incorporating QDs in nanofibers as an auxiliary light harvester, improving the performance of these devices from 5.9 to 7.4%. This strategy offers a viable path of controlling the arrangements of various functional moieties in solid-state devices.